2011
DOI: 10.1111/j.1751-7893.2010.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Jumping to conclusions’ in first-episode psychosis

Abstract: JTC is a phenomenon common in many people in first-episode services. In this large cohort sample, no clear associations with symptoms or other psychological processes were evident. Hence, the reason people JTC is still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 27 publications
7
37
2
1
Order By: Relevance
“…Both nonclinical and clinical participants with delusions adjust their answers accordingly when presented with a more difficult task, requesting more pieces of evidence before reaching a decision (Dudley et al, 1997b(Dudley et al, , 2011White and Mansell, 2009). This indicates that the JTC bias is a data-gathering bias rather than impulsivity.…”
Section: The Specificity Of the Jtc Bias: Emotional Saliency And Diffmentioning
confidence: 99%
See 2 more Smart Citations
“…Both nonclinical and clinical participants with delusions adjust their answers accordingly when presented with a more difficult task, requesting more pieces of evidence before reaching a decision (Dudley et al, 1997b(Dudley et al, , 2011White and Mansell, 2009). This indicates that the JTC bias is a data-gathering bias rather than impulsivity.…”
Section: The Specificity Of the Jtc Bias: Emotional Saliency And Diffmentioning
confidence: 99%
“…Not all individuals with delusions demonstrate the JTC bias, and the bias is also present in nonpsychiatric populations. Approximately 40% of individuals diagnosed with first-episode psychosis (FEP; Dudley et al, 2011) and 20% of a nonclinical population demonstrated the JTC bias .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many subsequent studies have confirmed this finding (for a review see Garety & Freeman, 2013). However, in much the same way as with theory of mind impairment, these studies have struggled to demonstrate an association with presence or severity of delusions (Dudley et al, 2011; Falcone et al, 2015; Freeman et al, 2014; Garety et al, 2013; Langdon, Ward, & Coltheart, 2010; Lincoln, Ziegler, Mehl, & Rief, 2010; Menon, Pomarol-Clotet, McKenna, & McCarthy, 2006; Moritz & Woodward, 2005; Mortimer et al, 1996; Ochoa et al, 2014; Peters, Thornton, Siksou, Linney, & MacCabe, 2008; So et al, 2012). …”
Section: Theories Of Delusionsmentioning
confidence: 99%
“…The sample sizes in these studies have increased [13]. In addition, the range of groups that have been considered has expanded so that studies have been undertaken with people in their first psychotic episode [14], as well people in more acute, chronic and remitting states [15,16]. …”
Section: Introductionmentioning
confidence: 99%